The new subversive geranium: some notes on the management of additional troubles in maximum security prisons - Liebling, Alison (The British journal of sociology, 2019)
In this paper, we revisit King and McDermott's 1990 article on the social construction of ‘control problem’ prisoners and their management in high security prisons, in the light of our recent research on the location and building of trust in contemporary high security prisons. We examine how religious and race identities are now deeply implicated in the construction of risk, and we describe the procedures for and some of the consequences of managing the new risks of radicalization and extremist violence in prison. The analysis is based on observations and interviews with staff and prisoners in two main and two supplementary maximum‐security prisons in England and Wales.